1997
DOI: 10.1002/(sici)1097-010x(19971215)279:6<562::aid-jez4>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of binding of the annelidan myoactive peptides, GGNG peptides, to tissues of the earthworm,Eisenia foetida

Abstract: The GGNG peptides are myoactive peptides which we have isolated from several species of annelids. Two types of peptides have been isolated as GGNG peptides: earthworm excitatory peptides (EEP) and leech excitatory peptide (LEP). The EEP and LEP are highly homologous with each other but act specifically on earthworms and leeches, respectively. To approach the mechanism of the specific action, we attempted to characterize the receptors for EEP in the earthworm Eisenia foetida, from which EEP have been isolated, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2025
2025

Publication Types

Select...
2
2
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The behavioral effect of a single type of peptide on different animals has only been tested for FMRFamide and its orthologue FLRFamide and the different studies showed some species-specific effects in different trochozoan larvae (41,(43)(44)(45). The influence of EP on locomotion of L. longissimus larvae and the broad expression in the brain and prominent ventral nerve cord of the juveniles stands in contrast to the myo-excitatory effect of EPs in different adult/juvenile annelid (6,23,24,26) and mollusc (25) species and the repeated association of EPs and CCHamides with feeding or the digestive system in annelids (6,23,24,26,64), molluscs (25,65) and insects (5,7,(16)(17)(18)(19)(20)(21)(22)) (see also table 2). This suggests that the degree of functional conservation can vary depending on the type of peptide, the animal taxon or the developmental stages and that also functionally more conserved peptides like the EP/CCHamides can show plasticity in their behavioral association.…”
Section: Functional Association Of Peptides Can Vary During Evolutionmentioning
confidence: 99%
“…The behavioral effect of a single type of peptide on different animals has only been tested for FMRFamide and its orthologue FLRFamide and the different studies showed some species-specific effects in different trochozoan larvae (41,(43)(44)(45). The influence of EP on locomotion of L. longissimus larvae and the broad expression in the brain and prominent ventral nerve cord of the juveniles stands in contrast to the myo-excitatory effect of EPs in different adult/juvenile annelid (6,23,24,26) and mollusc (25) species and the repeated association of EPs and CCHamides with feeding or the digestive system in annelids (6,23,24,26,64), molluscs (25,65) and insects (5,7,(16)(17)(18)(19)(20)(21)(22)) (see also table 2). This suggests that the degree of functional conservation can vary depending on the type of peptide, the animal taxon or the developmental stages and that also functionally more conserved peptides like the EP/CCHamides can show plasticity in their behavioral association.…”
Section: Functional Association Of Peptides Can Vary During Evolutionmentioning
confidence: 99%
“…Although earthworm excitatory peptides and LEP are structurally very similar to each other, they do not show cross-reactivity . This specific action of LEP and earthworm excitatory peptides has been shown to be attributable to their different binding affinities for receptors in membrane preparations (Niida et al 1997). Kawano et al (1996) have cloned cDNAs for earthworm excitatory peptides and LEP and found that their nucleotide sequences are quite different from each other, except for the regions encoding the peptides.…”
Section: Introductionmentioning
confidence: 99%